Pectin Extraction from Ambon Banana (Musa Paradisiaca Var. Sapientum) Peel and Its Application for Gummy Jelly - Muhammad Fakih Kurniawan; Distya Riski Hapsari; R. Siti Nurlaela; Nuraimy Citra (Indonesian Journal of Applied Research (IJAR), 2023)
Considered a waste, the peel of the Ambon banana (Musa paradisiaca var. sapientum) contains an appreciable amount of pectin. Pectin can be used to produce gummy jelly products with the addition of carrageenan as a stabilizer. The manufacture of gummy jelly must consider a good proportion of pectin and carrageenan. This study aimed to extract pectin from Ambon banana peel and determine the best formulation of gummy jelly incorporated with the pectin and carrageen as a gelling agent. Pectin was extracted from Ambon banana peel and then analyzed for yield, ash content, equivalent weight, methoxyl content, galacturonic content, and degree of esterification. Gummy jelly was made with various levels of pectin (0.5%, 1%, 1.5%, 2%) and carrageenan (1%, 1.5%, 2%). The product was analyzed for water content, ash content, reducing sugar content, sensory quality test, and hedonic test. The characteristics of pectin, i.e., moisture content, ash content, galacturonic acid content, methoxyl content, and the degree of esterification, were compared to IPPA (International Pectin Producer Association) standard. Meanwhile, the gummy jelly samples were confirmed to comply with the requirements of SNI Soft Candy 3547-2-2008 for water content, ash content, and reduced sugar content. In addition, we found that a higher concentration of pectin in the formulation led to a lower chewiness, decreasing the panelist’s preference. Considering the chemical and sensory properties of the candy, the most desirable formulation was achieved at the ratio of pectin and carrageenan 1.5%:2%. Pectin from banana peels can be used as an ingredient in gummy jelly. This work suggested further studies on the candy's textural properties, such as gumminess and chewiness.